THE CONCEPT OF PROPERTY RIGHTS IN THE REPUBLIC OF UZBEKISTAN: THE MAIN ASPECTS OF PROPERTY RIGHTS, OWNERSHIP, USE AND DISPOSITION OF PROPERTY - Isroilova Saxodat Otabek qizi; Farmonaliyeva Nargiza Inomjon qizi (Bright Mind Publishing, 2025)
This article analyzes the basis for the emergence of property rights, the legal regulation of property rights based on the norms existing in our legislation, the legal basis for the emergence of property rights, and the right of ownership of property are described.
Keywords: Property, ownership, use of property, possession, management, private property, legal protection, illegal possession.